Legal Analysis of Criminal Regulations in Cases Criminal act Child Abuse Under Law Child Protection Act - Maekal Ananta Pratama Ginting; Hasdiana Juwita Bintang; Henry Aspan (International Journal of Sociology and Law, 2024)
In Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection, there is an article that prohibits obscene acts, which is regulated in Article 76E which reads: "Everyone is prohibited from committing violence or threats of violence, coercing, committing tricks, committing a series of lies, or persuading children to commit or allow obscene acts to be committed." Furthermore, Article 76D which reads: "Everyone is prohibited from committing violence or threats of violence to force a child to have intercourse with him or with another person This research was conducted with the aim of finding out how to protect the law for children who are victims of criminal acts of obscenity and how to prove and apply the law to criminal acts of obscenity committed by children. . The research method conducted in this study is a normative juridical research method so that it can be concluded as follows: 1. Child protection is regulated in Law Number 23 of 2002. In addition to Law No. 23 of 2002 concerning Child Protection in protecting victims of child molestation, Law No. 13 of 2006 concerning the Protection of Witnesses and Victims can also protect victims of child abuse and victims of other criminal acts.2. Evidence in the crime of obscenity uses evidence in accordance with the Criminal Code. The valid evidence according to Law No. 8 of 1981 is regulated in Article 184 of the Criminal Procedure Code which consists of witness statements, expert statements, letter of recommendation, and information of the defendant. In the application of the law against child molesters, Article 82 of Law Number 23 of 2002 concerning Child Protection can be applied by using the mechanism and system of child justice, namely Law Number 11 of 2012 concerning the Child Criminal Justice System.